KESADARAN DAN SELF -DIRECTED LEARNING SEBAGAI MODEL PEMBELAJARAN ALTERNATIF DALAM ERA NEOLIBERALISME - Istiyani, Dwi (Forum Tarbiyah, 2009)
Learning should be ideally done with full awareness of the learner themselves, since through self-awareness on the next stage in the learning process will familiarize learners to be able to study independently, or with which it has would foster soul awareness in order to be independent in learner’s study or life. Consciousness and self-directed learning (SDL) is an essential part of learning solutions. Both these concepts can become an alternative model in dealing with education issues in the context of neoliberalizm. Education is part of the victims of neoliberalizm, due to the policy of privatization and reduced budgets for education. Hence as one of the steps that is representative enough in learning is by providing principles of awareness and stimulating independent learning on learner.